Synergistic effects of climate and land‐use change influence broad‐scale avian population declines - Northrup, Joseph M.; Rivers, James W.; Yang, Zhiqiang; Betts, Matthew G. (Global change biology, 2019)
Climate and land‐use changes are expected to be the primary drivers of future global biodiversity loss. Although theory suggests that these factors impact species synergistically, past studies have either focused on only one in isolation or have substituted space for time, which often results in confounding between drivers. Tests of synergistic effects require congruent time series on animal populations, climate change and land‐use change replicated across landscapes that span the gradient of correlations between the drivers of change. Using a unique time series of high‐resolution climate (measured as temperature and precipitation) and land‐use change (measured as forest change) data, we show that these drivers of global change act synergistically to influence forest bird population declines over 29 years in the Pacific Northwest of the United States. Nearly half of the species examined had declined over this time. Populations declined most in response to loss of early seral and mature forest, with responses to loss of early seral forest amplified in landscapes that had warmed over time. In addition, birds declined more in response to loss of mature forest in areas that had dried over time. Climate change did not appear to impact populations in landscapes with limited habitat loss, except when those landscapes were initially warmer than the average landscape. Our results provide some of the first empirical evidence of synergistic effects of climate and land‐use change on animal population dynamics, suggesting accelerated loss of biodiversity in areas under pressure from multiple global change drivers. Furthermore, our findings suggest strong spatial variability in the impacts of climate change and highlight the need for future studies to evaluate multiple drivers simultaneously to avoid potential misattribution of effects. Birds in the Pacific Northwest of the United States declined most strongly in response to loss of mature forest, followed by loss of early seral forest. Declines from loss of mature forest were strongest in landscapes that had become drier over time and declines from loss of early seral forest were strongest in landscapes that had warmed over time. This is some of the first empirical evidence for synergistic effects of the two greatest threats to biodiversity and suggest the potential for underestimation of biodiversity declines from studies focusing on only climate or land‐use change in isolation.